Inflammatory Myofibroblastic Tumors in Children: A Clinical Retrospective Study on 19 Cases - Da, Min; Qian, Bo; Mo, Xuming; Xu, Cheng; Wu, Haiyan; Jiang, Bin; Peng, Wei; Qi, Jirong; Sun, Jian; Wu, Kaihong (Frontiers in Pediatrics, 2021)
Abstract Background: Inflammatory myofibroblastic tumor (IMT) is a kind of mesenchymal tumor characterized by differentiation of myofibroblast spindle cells and prominent infiltration of plasmocytes and/or lymphocytes. We conducted a retrospective study to evaluate the clinical features and treatment alternatives of childhood inﬂammatory myoﬁbroblastic tumors. Methods: A total of 19 patients who were pathologically diagnosed with IMT between December 2008 and October 2018 were included. Collected data were demographic information, main complaints, tumor characteristics, treatment, pathological results, immunohistochemical analysis, and prognosis. Results: The male/female ratio was 13:6. The mean age at disease onset was 44.9 ± 33.9 months (range 4 to 111 months). The mean tumor size was 6.5 ± 4.0cm (range1.2 cm to 17.0 cm). The most common site was the abdomen (13/19). The most commonly used detection tool was CT. Eleven patients (57.9%) had aggressive tumor growth, including eight receiving extensive resection and three receiving palliative resection due to high local invasiveness and postoperative chemotherapy. Eight cases whose tumors were completely enveloped received complete resection. Immunohistochemistry was performed for 17 patients and ALK positivity was found in 11 patients. Despite three children lost to follow-up, sixteen patients were followed up for 6 to 132 months (average 63.9 months, median 66 months). Of which, twelve children survived with no evidence of IMT, and four cases (21%) showed local recurrences (two of them died). No distant metastasis was detected. Conclusions: IMT is rare in children with various locations, mostly appearing in the abdomen. whether the tumor could be completely removed, the location and the invasiveness of surrounding tissues might be highly prognosis-related.